EVALUATION OF RADIATION DOSE RATE OF RSG-GAS REACTOR - Hamzah, Amir; Adrial, Hery; Subiharto, Subiharto (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2018)
EVALUATION OF RADIATION DOSE RATE OF RSG-GAS REACTOR. The RSG-GAS reactor has been operated for 30 years. Since the nuclear reactor has been operated for a long time, aging process on its components may occur. One important parameter for maintaining the safety level of the RSG-GAS reactor is to maintain radiation exposure as low as possible, especially in the working area. The evaluation results should be able to demonstrate that the radiation exposure of the RSG-GAS is still safe for workers, communities and the surrounding environments. The purpose of this study is to evaluate radiation exposure in the working area to ensure that the operation of RSG-GAS is still safe for the next 10 years. The scope of this work is confirming the calculation results with the measured radiation dose in the RSG-GAS reactor working area. Measurement of radiation exposure is done by using the installed equipments at some points in the RSG-GAS working area and a portable radiation exposure measurement equipment. The calculations include performance of a modeling and analysis of dose rate distribution based on the composition and geometry data of RSG-GAS by using MCNP.  The analysis results show that the maximum dose rate at Level 0 m working area of RSG-GAS reactor is 3.0 mSv/h with a deviation of 6%, which is relatively close to the measurement value. The evaluation results show that the dose rate in RSG-GAS working area is below the limit value established by the Nuclear Energy Regulatory Agency of Indonesia (BAPETEN) of 10 mSv/h (for the average effective dose of 20 mSv/year). Therefore, it is concluded that the dose rate in RSG-GAS working area is safe for personnel..Kata kunci: dose rates, RSG-GAS, radiation safety, MCNP.